The Crime-Fraud Exception to the Attorney-Client Privilege: Communications That Are Not Privileged - Hunter, Richard J.; Shannon, John H. (Advances in Social Sciences Research Journal, 2024)
In three previous articles, “Assessing Confidentiality in the Lawyer-Client Relationship: A Client Perspective” (2022a), “Avoiding Common Conflicts of Interest in the Lawyer-Client Relationship” (2022b), and “The Lawyer-Client Relationship: Fee Arbitration” (2022c), the authors have described various aspects of the lawyer-client relationship. In this article, the authors describe an important exception to the principle of confidentiality found in the crime-fraud doctrine which permits a court to breach lawyer-client confidentiality upon the proper showing.